2019
DOI: 10.3390/toxins11030157
|View full text |Cite
|
Sign up to set email alerts
|

Proanthocyanidins Alleviates AflatoxinB1-Induced Oxidative Stress and Apoptosis through Mitochondrial Pathway in the Bursa of Fabricius of Broilers

Abstract: Aflatoxin B1 (AFB1) is a serious threat to the poultry industry. Proanthocyanidins (PCs) demonstrates a broad range of biological, pharmacological, therapeutic, and chemoprotective properties. The aim of this study was to investigate the ameliorative effects of PCs against AFB1-induced histopathology, oxidative stress, and apoptosis via the mitochondrial pathway in the bursa of Fabricius (BF) of broilers. One hundred forty-four one-day old Cobb chicks were randomly assigned into four treatment groups of six re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(26 citation statements)
references
References 49 publications
(56 reference statements)
0
24
0
2
Order By: Relevance
“…AFB1 inhibited the transcription of BCL2 in the kidney tissues of broilers and promoted the transcription of P53, BAX, BAK1, CYC, CASP9, and CASP3, and induced kidney cell apoptosis via the mitochondrial pathway. These findings indicate that AFB1 may activate the mitochondria-mediated apoptosis pathway (57). However, PCPC treatment inhibited the overexpression of P53, BAX, BAK, CYC, CASP9, and CASP3 induced by AFB1, whereas upregulation of BCL2 was observed.…”
Section: Discussionmentioning
confidence: 77%
“…AFB1 inhibited the transcription of BCL2 in the kidney tissues of broilers and promoted the transcription of P53, BAX, BAK1, CYC, CASP9, and CASP3, and induced kidney cell apoptosis via the mitochondrial pathway. These findings indicate that AFB1 may activate the mitochondria-mediated apoptosis pathway (57). However, PCPC treatment inhibited the overexpression of P53, BAX, BAK, CYC, CASP9, and CASP3 induced by AFB1, whereas upregulation of BCL2 was observed.…”
Section: Discussionmentioning
confidence: 77%
“…The 10% tissue homogenates were prepared from collected liver samples following our previously reported procedure [ 6 ]. The bicinchoninic acid determination kit was used to measure the protein concentration of tissue homogenate.…”
Section: Methodsmentioning
confidence: 99%
“…Currently, approximately 4.5 billion people are in danger of being exposed to aflatoxins, which cause 4.6–28.2% of all occurrences of hepatocellular carcinoma worldwide [ 4 , 5 ]. Aflatoxin B 1 (AFB 1 ) is the most potent liver carcinogen among the aflatoxins, and it has been categorized as a Class I carcinogen by the International Agency for Research on Cancer (IARC) [ 6 ]. Additionally, AFB 1 is reported to cause severe health issues, including growth retardation, hepatotoxicity, neurotoxicity, teratogenicity, mutagenicity and immunotoxicity in humans and animals [ 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…It was also demonstrated that detannin-caffeinated coffee is significantly more sensitive to aflatoxin contamination than regular coffee [56]. More recently, it has also been demonstrated that some condensed tannins (proanthocyanidins) could alleviate AFB1-induced oxidative stress and apoptosis in broilers [57]. In fact, AFB1 and some of its metabolic precursors, such as norsolorinic acid and versicolorins, are highly oxygenated molecules and thus are subjected to redox regulation [58].…”
Section: Effect Of Condensed Tannins On Fungal Growth and Aflatoxin B1 Productionmentioning
confidence: 99%